1989
DOI: 10.1073/pnas.86.18.7228
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels mediate the transition between tonic and phasic firing in thalamic neurons.

Abstract: Thalamic neurons undergo a shift from tonic to phasic (burst) firing upon hyperpolarization. This state transition results from deinactivation of a regenerative depolarizing event referred to as the low-threshold spike. Isolated adult guinea pig thalamic (dorsal lateral geniculate) neurons exhibited low-threshold spikes that could be blocked by low concentrations of nickel but were unaffected by the dihydropyridine nimodipine. Whole-cell voltage-clamp recordings from these cells demonstrated a low-threshold, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 46 publications
8
111
2
Order By: Relevance
“…The rhythmic bursting of thalamic neurons is specifically dependent on the T-type calcium channel, as demonstrated by many in vitro studies (Jahnsen and Llings, 1984;Steriade and Llinas, 1988;Coulter et al, 1990;Avanzini et al, 1992). Suzuki and Rogawski (1989) showed that these thalamic oscillations could be blocked by T-type calcium channel blockers. Coulter et al confirmed the involvement of T-type channels in oscillations and in absence epilepsy by showing that ESM, a drug that selectively protects against absence epilepsy, specifically inhibits T-type channels (Coulter et al, 1989a(Coulter et al, ,1989b); thus ample evidence shows that T-type calcium channel blockade inhibits thalamic oscillations.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The rhythmic bursting of thalamic neurons is specifically dependent on the T-type calcium channel, as demonstrated by many in vitro studies (Jahnsen and Llings, 1984;Steriade and Llinas, 1988;Coulter et al, 1990;Avanzini et al, 1992). Suzuki and Rogawski (1989) showed that these thalamic oscillations could be blocked by T-type calcium channel blockers. Coulter et al confirmed the involvement of T-type channels in oscillations and in absence epilepsy by showing that ESM, a drug that selectively protects against absence epilepsy, specifically inhibits T-type channels (Coulter et al, 1989a(Coulter et al, ,1989b); thus ample evidence shows that T-type calcium channel blockade inhibits thalamic oscillations.…”
Section: Resultsmentioning
confidence: 92%
“…Bay K 8644, a dihydropyridine derivative, increases the opening probability of a particular subclass of calcium channels, the L-type channel, thereby promoting voltage-dependent calcium influx (Bernath, 1992). On the other hand, nimodipine also belongs to the class of dihydropyridines, but this centrally active drug acts as a calcium antagonist by blocking the voltage-dependent L-type calcium channels (Meyer et al, 1987;Suzuki and Rogawski, 1989). Spedding and Paoletti (1992) suggest that BAY K 8644 and nimodipine are rather selective for the L-type calcium channels.…”
mentioning
confidence: 99%
“…Considerable evidence suggests that spike-wave discharges are produced by synchronized oscillations of cortical, reticular thalamic, and corticothalamic neurons (92,136,378). Spike-wave discharges of corticothalamic neurons are in part mediated by T-type channels that produce LTS (93,277,377,387). Ethosuximide is a first-line drug in the treatment of absence epilepsy (193).…”
Section: B Antiepilepticsmentioning
confidence: 99%
“…The rhythmic volleys traveling along the reticular cell axons induce GABA A -and GABA B -mediated hyperpolarizing inhibitory postsynaptic potentials (IPSPs) in relay neurons. As the membrane potential hyperpolarization of the relay neurons decays toward the resting level, a T-type Ca 2+ current is generated that triggers bursts of action potentials (76)(77)(78)(79)(80). In addition, a noninactivating Na + -current component may act synergistically with the T-type Ca 2+ current in the generation of bursting (81).…”
Section: Pathophysiology Of Absence Attacksmentioning
confidence: 99%